Empowering through Solidarity: The Role of Women’s Cooperatives in the Integration of Syrian Refugee Women in Türkiye (Third Sector Social Economic Review, 2025)
The Syrian Civil War, triggered one of the largest humanitarian crises of the 21st century, displacing nearly 35 million Syrians. As of 2024, Türkiye hosts approximately four million Syrians. Among various strategies proposed for facilitating refugee integration, women’s cooperatives remain an underexplored area within the literature. This article explores the potential role of women’s cooperatives in supporting displaced Syrian women’s integration processes. Rather than focusing on the challenges faced by these women, the study centres on the transformative capacity of cooperatives as community-based spaces that offer economic, social, and cultural pathways to integration. Drawing on qualitative fieldwork and relevant academic literature, this article contends that through their inclusive, participatory, and solidarity-based models, women’s cooperatives can foster economic empowerment, cultural interaction, and social cohesion among Syrian and Turkish women. By spending time in these cooperatives, women not only gain income-generating skills but also engage in intercultural dialogue and shared daily practices, which organically contribute to cultural integration. The findings also reveal structural limitations such as dependency on external funding, lack of institutional support, and inadequate long-term policy frameworks. Nevertheless, the article argues that women’s cooperatives represent a promising grassroots model for sustainable refugee integration when supported through inclusive and gender-sensitive public policies. In contributing to debates on migration, gender, and integration, this study sheds light on an overlooked but significant site of resilience, solidarity, and empowerment: women’s cooperatives.
Keywords: Cultural Integration; Economic Integration; Gender Studies; Refugee; Refugee Crisis; Refugee Integration; Syrian Civil War; Womens Cooperatives; Women's Empowerment